Payment automation with HSBC for Robi Axiata Limited - Abeysekara, Appu Gammahelage Upeksha Subodhanee (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.